2014
DOI: 10.1063/1.4905002
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-based transparent flexible heat conductor for thermally tuning nanophotonic integrated devices

Abstract: Graphene, a well-known two-dimensional sheet, has attracted strong interest for both fundamental studies and applications. Due to its high intrinsic thermal conductivity, graphene has many potential applications in thermal management, such as in heat spreaders and flexible heaters. In this paper, a graphene-based transparent flexible heat conductor for nanophotonic integrated devices is demonstrated. The graphene heat conductor is designed to deliver heat from a non-local traditional metal heater to nanophoton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 32 publications
0
54
0
Order By: Relevance
“…Thermally induced inhomogeneous refractiveindex distribution of the cladding polymer controllably attenuates the graphene based long-range surface plasmon waveguide for light modulation. b, Schematic of a thermo-optic modulator based on graphene heat conductor 116 . c, Schematic of a graphene based Faraday-rotator and d, its Faradayrotation response at different magnetic fields 119 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thermally induced inhomogeneous refractiveindex distribution of the cladding polymer controllably attenuates the graphene based long-range surface plasmon waveguide for light modulation. b, Schematic of a thermo-optic modulator based on graphene heat conductor 116 . c, Schematic of a graphene based Faraday-rotator and d, its Faradayrotation response at different magnetic fields 119 .…”
mentioning
confidence: 99%
“…Graphene based transparent flexible heat conductors also have been used to deliver localized heat for light modulation in a silicon based Mach-Zehnder interferometer (Fig. 5b) and a micro-disk resonator 116 . Another recent study used an opticallycontrolled graphene heater to change the fibre's refractive index in a fibre based Mach-Zehnder interferometer for all-fibre phase shifter and switching 117 .…”
mentioning
confidence: 99%
“…Yu et al demonstrated thermal tuning in both a Mach-Zehnder interferometer and a micro-disk resonator using graphene to conduct heat from a non-local metal heater ( Figure 4E) [61]. Graphene, itself, can also be used in place of a traditional metal heater as demonstrated by Gan et al [71].…”
Section: (E)mentioning
confidence: 99%
“…[21], graphene-based transparent nano-heater on SOI nanowires was proposed and demonstrated for the first time. In this design, the graphene nano-heater is placed to contact directly with the silicon core (see Fig.…”
Section: Soi Nanowire With a Graphene Nano-heatermentioning
confidence: 99%
“…In Ref. [20], we demonstrated a thermally tunable silicon photonic devices with graphene thermal conductor. We also proposed a thermally tuning silicon micro-disk resonator with graphene transparent nano-heaters for the first time [21].…”
Section: Introductionmentioning
confidence: 99%